Diffusion kinetics of Furfural adsorption onto Activated Carbon - H. Sulaymon, Abbas; W. Alhayali, Kawther; Waadallah Ahmed, Ammar (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
A range of batch experiments were carried out for the estimation of the key process parameters in adsorption of Furfural from aqueous solution onto activated carbon in fixed-bed adsorber. A batch absorber model has been used to determine the external mass transfer coefficient (kf) which equal to 6.24*10-5 m/s and diffusion coefficient (Dp) which equal to 9.875*10-10 m2/s for the Furfural system. The Langmuir model gave the best fit for the data at constant temperature (30oC). The pore diffusion mathematical model using nonlinear isotherm provides a good description of the adsorption of Furfural onto activated carbon.